Corporate Governance Research Mapping with Bibliometric - Rikah, Rikah (Ann Publisher, 2024)
This paper intends to conduct a comprehensive analysis of articles focusing on the field of corporate governance from various studies that have been published in the Scopus database. A bibliometric approach is used to identify common patterns in research related to corporate governance. The research is based on an analysis of 2,202 articles from 2013 to 2022 and indexed in the Scopus database. The findings reveal that research on corporations is still dominated by countries such as the United States, the United Kingdom, and Malaysia. Some keywords such as